HIGH PREVALENCE OF SUBJECTS WITH HIGH CARDIOVASCULAR RISK IN COMMUNITY PHARMACIES – HIC RHODUS. HIC SALTO. PHYSICIAN-PHARMACIST COLLABORATIVE PROJECT OF THE CROATIAN SOCIETY OF HYP. (June 2018) - Jelakovic, A.; Brozovic, M.; Dobrincic, Z.; Domislovic, V.; Djapic, K.; Lugovic, N.; Mrsic, M.; Radovcic, M.; Skopic, O. Velkovski; Jelakovic, B.
Abstract : Objective: Pharmacists are highly accessible healthcare professionals and it has been reported that community pharmacist-led interventions improved patients' BP control and outcomes. The aim of this study was to identify subjects who may benefit from such interventions by analyzing characteristics and global cardiovascular (CV) risk in sample of subjects who visited pharmacies in Zagreb County on World Hypertension Day 2017. Design and method: Blood pressure (BP) and total serum cholesterol (TC) (Roche Accutrend Plus;not always fasting) were measured by local pharmacists. In total, 906 subjects (369 M, 546 F, mean age 53.7, range 21–74) who visited pharmacies for various reasons and agreed to participate were enrolled. BP was measured twice after rest of 5 minutes in seated position using Omron M6 device. Subjects were divided in 2 subgroups depending on smoking habits. There is a risk of sampling bias as only those who agreed to participate were included. Demographic and anthropometric data; cardiovascular risk factors; data on salt intake and opinion about the usefulness of smart-phone applications in hypertension were collected. Results: BP > 140/90 mmHg was found in 34.7% (M vs. F 41.9% vs. 30.0%; x2 = 13.04; p < 0.0001, ), TC > 5 mmol/l in 29.1% (M vs. F 36.9% vs. 24.0%; x2 = 15.8; p < 0.0001), and there were 34.9% smokers (M vs. F 38.6% vs. 32.6%; p > 0.05). Heart Score > 5% was determined in 20.5% subjects, and 6.3% had risk higher than 10%. Conclusions: Subjects with elevated BP, TC and high global CV risk regularly visit pharmacies. Most of subjects had modifiable risk factors like hypertension, smoking and obesity. Pharmacists should have more emphasized role in patient education about life-style changes and could contribute to better drug adherence. Additionally, public health actions organized in pharmacies could identify subjects with high global CV risk who should be refered to physicians.